Pengaruh Penerapan e-Government Pada Pembangunan Smart City di Kabupaten Sumenep - Alfiyah, Nur Inna (Universitas Islam Malang, 2019)
Based on Presidential Instruction Number 3 of 2003 concerning National Policies and Strategies regarding E-government. Demand governments at various levels to take the necessary steps according to their respective duties, functions and authorities for the implementation of e-government development programs. To apply e-government in Sumenep Regency, the local government began to take steps in responding to the presidential decree issued by the central government by launching the g-online program. The g-online program is able to provide benefits to local government organizations in integrating public service systems. As technology and information are developing rapidly, government programs are undergoing renewal, with the birth of the smart city development program as a step towards strengthening the implementation of e-government in the regional government of Sumenep Regency. So this writing aims to answer how the influence of e-government in the construction of smart cities in Sumenep Regency. The method used in this research is an explanative descriptive method with the support of library or library data.